Variation of Irrigation Methods and Fertiliser Level in Cultivation of Shallot on Rainfed Land - Sahidatun Fahima; Murtiningrum Murtiningrum; Ngadisih Ngadisih; Muhamad Khoiru Zaki; Rizki Maftukhah; Fransiska Maria Aprilya Nana (agriTECH, 2026)
Drought is a major challenge limiting agricultural productivity, especially in rainfed land. This problem prompted the development of adaptive and efficient cultivation strategies, particularly in the selection of irrigation methods and fertilizer levels.  Therefore, this research aimed to determine the effect of irrigation methods (mist irrigation and drip irrigation) and NPK fertilizer levels (0 kg/ha, 500 kg/ha, and 1000 kg/ha) on shallot yield and water use efficiency. Drought index analysis and field experimentation were used to evaluate adaptive irrigation management under dryland conditions. Meteorological and agronomic drought were characterized using the Standardized Precipitation Index (SPI) and Standardized Precipitation Evapotranspiration Index (SPEI) derived from NASA POWER data. Field data were collected using an Automatic Weather Station (AWS) and calibrated soil moisture sensors, while evapotranspiration was calculated with the FAO Penman–Monteith method. The data were analyzed using a split-plot design with two-way Analysis of Variance (ANOVA) and Pearson correlation to determine treatment effects and relationships among parameters. The results showed that irrigation methods significantly affected soil physical properties, especially porosity and moisture content, which further impacted crop yield. Furthermore, the combination of mist irrigation with a 1000 kg/ha NPK rate produced the highest yield and water use efficiency. The water efficiency values obtained were Crop Water Productivity (CWP) and Irrigation Water Use Efficiency (IWUE) of 10.45 kg/m³ and 12.07 kg/m³, respectively. These results showed that proper irrigation methods and fertilizer rates could increase crop yield and water use efficiency in rainfed lands.